М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
oksankavelsh
oksankavelsh
13.06.2020 16:42 •  Алгебра

Решите уравнение (5-x^(-1))^(-1)=2^(-2) 14

👇
Ответ:
верника3
верника3
13.06.2020


Решите уравнение (5-x^(-1))^(-1)=2^(-2) 14
4,6(32 оценок)
Ответ:
Wika201720062006
Wika201720062006
13.06.2020

...........................


Решите уравнение (5-x^(-1))^(-1)=2^(-2) 14
4,8(68 оценок)
Открыть все ответы
Ответ:
olgamorozkina19
olgamorozkina19
13.06.2020
(a^2+b^2)(a^4-(ab)^2+b^4) + (a^3-b^3)(a^3+b^3)=2a^6 (a^2+b^2)(a^4-(ab)^2+b^4) = a^6+b^6 – формула. n^3+m^3 = (n+m)(n^2-nm+m^2)(a^3-b^3)(a^3+b^3) = a^6-b^6 – такжеформула. (n-m)(n+m) = n^2-m^2В итоге: a^6+b^6+a^6-b^6 = 2a^62.       (a^2+b^2)(c^2+d^2) = (ac+bd)^2+(ad+bc)^2(a^2+b^2)(c^2+d^2) = (ab)^2+(ad)^2+(bc)^2+(bd)^2 = (ac)^2+(ad)^2+(bc)^2+(bd)^2+2abcd–= ((ac)^2+2abcd+(bd)^2)+((ad)^2-2abcd+(bc)^2) = (ac+bd)^2+(ad-bc)^23.       (a^2+cb^2)(d^2+ce^2) =(ad+cbe)^2+c(ae-bd)^2(a^2+cb^2)(d^2+ce^2)=(ad)^2+c(ae)^2+c(bd)^2+(bce)^2=(ad)^2+c(ae)^2+c(bd)^2+(bce)^2+2abcde-2abcde=((ad)^2+(bce)^2+2abcde)+(c(ae)^2+c(bd)^2-2abcde)=(ad+bce)^2+(c((ae)^2+(bd)^2-2abde))=(ad+bce)^2+c(ae-bd)^2
4,7(67 оценок)
Ответ:
shum2
shum2
13.06.2020
а)sin 2x=√3 cos x
2sinxcosx-√3cosx=0
cosx(2sinx-√3)=0
cosx=0⇒x=π/2+πn,n∈Z
sinx=√3/2⇒x=(-1)^n*π/3+πk,k∈Z
б)sin 2x=√2 cos x
2sinxcosx-√2cosx=0
cosx(2sinx-√2)=0
cosx=0⇒x=π/2+πn,n∈Z
sinx=√2/2⇒x=(-1)^n*π/4+πk,k∈Z в)sin(0,5п+x)+ sin 2x=0
г)cos(0,5п+x)+ sin 2x=0
-sinx+2sinxcosx=0
-sinx(1-2cosx)=0
sinx=0⇒x=πn,n∈Z
cosx=1/2⇒x=+-π/3+2πk,k∈Z
д)sin 4x+√3 sin 3x+sin 2x=0
2sin3xcosx+√3sin3x=0
sin3x(2cosx+√3)=0
sin3x=0⇒3x=πn,n∈Z⇒x=πn/3,n∈Z
cosx=-√3/2⇒x=+-5π/6+2πk,k∈Z
е)cos 3x+sin 5x=sin x
cos3x+sin5x-sinx=0
cos3x+2sin2xcos3x=0
cos3x(1+2sin2x)=0
cos3x=0⇒3x=π/2+πn,n∈Z⇒x=π/6+πn/3,n∈Z
sin2x=-1/2⇒2x=(-1)^(k+1)*π/6+πk,k∈Z⇒x=(-1)^(n+1)*π/12+πk/2,k∈Z
4,4(63 оценок)
Это интересно:
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ